Conjugal bereavement effects on health and mortality at advanced ages - Gerard J. van den Berg; Maarten Lindeboom; France Portrait (Institute for the Study of Labor (IZA), 2006)
We specify a model for the lifetimes of spouses and the dynamic evolution of health, allowing spousal death to have causal effects on the health and mortality of the survivor. We estimate the model using a longitudinal survey that traces many health status aspects over time, and that is linked to register data on the vital status of the individuals. The model takes account of selectivity in partners' mortality and health evolution. We find strong instantaneous effects of bereavement on mortality and on certain aspects of health. Individuals lose on average 12 % of residual life expectancy after bereavement. Bereavement affects the share of healthy years in residual lifetime, primarily because healthy years are replaced by years with chronic diseases
urn:nbn:de:101:1-20090622290
Keywords: 330; Ehe; Sterblichkeit; Gesundheitsversorgung